2015
DOI: 10.1074/jbc.m114.619783
|View full text |Cite
|
Sign up to set email alerts
|

Constitutive Activation of Epidermal Growth Factor Receptor Promotes Tumorigenesis of Cr(VI)-transformed Cells through Decreased Reactive Oxygen Species and Apoptosis Resistance Development

Abstract: Background: Chronic exposure to Cr(VI) causes cell transformation. Results: Cr(VI)-transformed cells exhibit activated EGFR, reduced ROS generation, and development of apoptosis resistance. Conclusion: Constitutive activation of EGFR promotes tumorigenesis of Cr(VI)-transformed cells.Significance: The findings provide a new understanding on carcinogenic mechanisms of not only Cr(VI) but also other metals, such as arsenic and nickel. It also can be used to formulate cancer prevention strategies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
35
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
3
3

Relationship

1
5

Authors

Journals

citations
Cited by 49 publications
(38 citation statements)
references
References 49 publications
0
35
0
Order By: Relevance
“…Ligand-induced EGFR dimerization triggers downstream signaling cascades including MAPK, PI3K-AKT, STAT, and PKC pathways. Our previous study has shown that constitutive activation of EGFR in Cr(VI)-transformed BEAS-2B cells is dependent on its ligand amphiregulin (12). Knockdown of EGFR reduced both tumor incidence and volume of Cr(VI)-transformed cells (12).…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Ligand-induced EGFR dimerization triggers downstream signaling cascades including MAPK, PI3K-AKT, STAT, and PKC pathways. Our previous study has shown that constitutive activation of EGFR in Cr(VI)-transformed BEAS-2B cells is dependent on its ligand amphiregulin (12). Knockdown of EGFR reduced both tumor incidence and volume of Cr(VI)-transformed cells (12).…”
Section: Discussionmentioning
confidence: 99%
“…Changes from normal cells to malignantly transformed cells are considered the first stage of metal-induced carcinogenesis (12,13). The development of malignantly transformed cells into tumor is the second stage.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations